Comparative effect of contextualized cubing and teacher-centred conventional instructional strategies on secondary school physics students’ academic achievement - Okeke, Uchenna Kingsley; Ramaila, Sam; Ukoh, Edidiong E. (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
In order to maximize students’ classroom learning experiences, there is a need to consider the informal knowledge they bring into the classroom. The context of students’ life plays an important role in the learning process. This study examined the comparative effect of contextualized-cubing and teacher-centred conventional instructional strategies on secondary school Physics students’ academic achievement. The study also examined the moderating effect of numerical ability. The constructivist theory provided the theoretical foundation. The empirical investigation adopted a quasi-experimental design and involved 107 Physics students from selected secondary schools in Ibadan Metropolis, Nigeria. Quantitative data was collected through the administration of Physics Achievement Test (PAT) and Students’ Numerical Ability Test (SNAT).Mixed model analysis was utilised by the study. The contextualised cubing instructional strategy was found to be effective in enhancing the students’ academic achievement in Physics irrespective of students’ numerical ability. The study, therefore, concludes that the contextualised-cubing instructional strategy is a suitable pedagogical strategy for Physics classroom instruction. Theoretical implications for contextually responsive pedagogy are discussed.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL Vol. 7 (3) (2023)
Keywords: Contextual Learning; Cubing instructional strategy; Numerical ability; Academic achievement; Teacher-centred conventional instructional strategy; Academic achievement -- Africa; Learning; Physics -- Study and teaching